Smartphone-Based Remote Control System for an Automated Red Onion Irrigation Robot - Irfin Sandra Asti; Fauzan Faadihilah Firdaus; Delila Cahya Permatasari; Erlillah Rizqi Kusuma Pradani; Muhammad Imbarothur Mowaviq; Rhezal Agung Ananto (G-Tech: Jurnal Teknologi Terapan, 2025)
Agriculture remains a vital sector in ensuring food security, economic stability, and rural livelihoods, particularly in developing countries such as Indonesia. Among various agricultural commodities, red onion (Allium cepa L.) plays a crucial role as one of the most consumed horticultural products and a key income source for farmers. However, its cultivation requires consistent soil moisture, and manual irrigation often results in inefficiency, labor intensity, and inconsistent watering. To address this problem, this study presents the design and implementation of a smartphone-based remote control irrigation robot for red onion cultivation. The system was developed using the ESP32 microcontroller integrated with the Blynk mobile application, enabling wireless control of both mobility and irrigation functions. Hardware components include a DC pump, motor driver, and relay module, supported by a 12-volt rechargeable battery as the power source. The robot’s mechanical frame, constructed from lightweight PVC and acrylic materials, was designed to provide stability and durability in agricultural environments. Performance tests showed that the robot operated reliably within a 20–30 m Wi-Fi range, achieved a movement speed of approximately 3 km/h, and produced water pressure of 160 psi, sufficient for red onion irrigation. Battery endurance reached 1 hour 40 minutes under continuous operation. In conclusion, the developed system demonstrates a practical, low-cost solution that integrates robotics and IoT technology to improve irrigation efficiency, reduce manual labor, and support sustainable water management in red onion farming.